Political, social, and economic capital analysis to winnings local general election in Malang 2013 - Jainuri (2014)
Winning a candidate and a contest in the election need to have is equity the political social and of budget, it. Political is Equity is relating to: (1) support from a party or coalition of parties; (2) Support from local political social elite, the religious elite and elite society community organizations. While is the extent to which the candidates have and functioning the network, community and organisations possessed.The next is the Equity of budget; it is how much money they had in sustaining his candidacy.This descriptive study using data collection techniques: documentation, observation and interview, wants to analyze the ability of six potential partner mayor of Malang in utilizing the tri Equity aforementioned in winning the election in the city of Malang in 2013.The three equity can effect a candidate in obtaining support will be obtained from the communities.The greater the turnover of equity possessed by the candidate the greater support will obtained.Suspected by AJI partner victory in the election of candidates and participate in being able to effectively and efficiently utilize the tri Equity. With such assumptions and hypotheses that this research was conducted in the hope of knowing the pragmatic reality of victory by AJI and its partner in effectively and efficiently utilizing political social equity, social equity, and equity of budget.